2021
DOI: 10.1155/2021/9479268
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Characteristics of ABCC8 Nonneonatal Diabetes Mellitus: A Systematic Review

Abstract: Objectives. Diabetes mellitus (DM) is a major chronic metabolic disease in the world, and the prevalence has been increasing rapidly in recent years. The channel of KATP plays an important role in the regulation of insulin secretion. The variants in ABCC8 gene encoding the SUR1 subunit of KATP could cause a variety of phenotypes, including neonatal diabetes mellitus (ABCC8-NDM) and ABCC8-induced nonneonatal diabetes mellitus (ABCC8-NNDM). Since the features of ABCC8-NNDM have not been elucidated, this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 131 publications
0
8
0
Order By: Relevance
“…Sulphonylureas shut down the K ATP channel via SUR1 receptor in pancreatic β cells, reverse the opening of the K ATP channel that causes ABCC8 mutation, and normalize the secretion of insulin. However, sulphonylureas do not work for all types of ABCC8-mutation related diabetes, a previous study found that 73.3% of the patients owing to ABCC8 variants with SUs got successful glucose control (15). The efficacy also depends on the structural and functional disorder caused by different mutations (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulphonylureas shut down the K ATP channel via SUR1 receptor in pancreatic β cells, reverse the opening of the K ATP channel that causes ABCC8 mutation, and normalize the secretion of insulin. However, sulphonylureas do not work for all types of ABCC8-mutation related diabetes, a previous study found that 73.3% of the patients owing to ABCC8 variants with SUs got successful glucose control (15). The efficacy also depends on the structural and functional disorder caused by different mutations (18).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of diabetic renal disease is low and is only seen in patients with three ABCC8 mutations. It should be noted that 34% of ABCC8neonatal diabetes mellitus (ABCC8-NDM) patients were associated with neurological disease, due to high expression of K ATP channel in both pancreas and nervous system, but the incidence of neurological complications was less than 1% in ABCC8-NNDM patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…ACAN variants have been reported to be associated with short stature in recent researches [26,27]. Additionally, ABCC8 was thought to be involved in the development of diabetes [28,29]. However, there was no direct evidence that ACAN and ABCC8 mutations were associated with the incidence of MSK.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heterozygous carriers of a mutation in the ABCC8 gene require long-term monitoring, as they present an increased risk for diabetes mellitus [39,40].…”
Section: Genetic Counselingmentioning
confidence: 99%